Investigating Geography Pre-Service Teacher’s TPACK Competencies in The Context of E-Learning - Muhammad Rizieq Fahmi; Syah Rizal; Khoirunnisaa’; Alfyananda Kurnia Putra (Future Space: Studies in Geo-Education, 2025)
Pre-service Geography teachers must be able to implement and develop technology in learning activities to effectively adapt to evolving educational demands, particularly in the context of the New Normal where e-learning has become integral to teaching and learning processes. TPACK (Technological Pedagogical and Content Knowledge) as a basic competency of pre-service Geography teachers in implementing e-learning in the New Normal era. Furthermore, the purpose of this study is to investigate the TPACK competencies of pre-service Geography teachers at the Universitas Negeri Malang and find a clear correlation between the TPACK constructions on pre-service Geography teachers. Then, this study uses a qualitative quantitative approach with a descriptive method with primary and secondary data collection. The population of this study were undergraduate students of the Geography Education Class of 2018 at Universitas Negeri Malang, while the sampling using the slovin method was 109 participants. Structural equation modeling (SEM) was employed to test the TPACK model, as it enables the analysis of complex relationships among the seven interrelated constructs within the framework. As a result, pre-service geography teachers have good TPACK competencies. The findings show that pre-service geography teachers are quite superior in the use of technology for learning (TPK). The focus of Content Knowledge (CK) that is being asked by pre-service geography teachers is in the scope of Anthroposphere. Meanwhile, the correlation between the TPACK constructs shows that each TPACK-forming factor has a varied correlation value. This revision clearly communicates the uneven distribution of competencies and highlights the need for targeted professional development, making the implications of the findings more explicit and actionable.